A historical note on an imported case of loiasis in Rio de Janeiro, Brazil, 1964 - Antonio Giardulli; Guilherme Dolanda Paulo Filho; Giovanni Nicola Urberto Italiano Colombini; Walter de Araújo Eyer-Silva; Carlos Alberto Basilio-de-Oliveira (Revista do Instituto de Medicina Tropical de São Paulo, 2011)
Loiasis is a filarial disease transmitted by the Chrysops spp. tabanid flies in West and Central Africa. It is most commonly diagnosed by the clinical manifestations of Calabar swellings (transient localized inflammatory edema) or, most dramatically, by the appearance of a migrating worm through the conjunctival tissues or the bridge of the nose. We report the case of a 35-year-old resident in the city of Rio de Janeiro who displayed a moving Loa loa in the bulbar conjunctival tissue two years after returning from a six-month trip to Uganda. Surgical removal of the worm was performed.